THE EXPANSION OF DISTANCE LEARNING (DL) IN BRAZILIAN HIGHER EDUCATION: TRENDS FOR THE BEGINNING OF THE NEXT DECADE - Morilhas, Leandro José (Future Studies Research Journal: Trends and Strategies, 2009)
In this article, the expansion of distance learning (DL) in Brazil’s Higher Education is analyzed with a view to addressing the following research query: How many schools, in Brazil, will offer undergraduate studies in the DL mode over the next five years? To this effect, bibliographical data was researched and historical series of variables were compiled – number of schools, of courses and of enrolled students, among other elements – to generate comparative graphs between the in loco (classroom) and the distance modes. Thus, the evolution of both types during the period studied is presented. Furthermore, a simple linear regression was used to correlate the variables ‘number of institutions’ and ‘time’, in order to extrapolate growth trends for the 2007-2011 period. Results point to a sharp expansion of DL, in all studied variables, and indicate that this may increase even further in the future. It also became evident that the growth of distance learning will have to overcome certain challenges, including better access to computers and to the Internet and the development of qualified personnel and of specific software to deal with it. Key words: Distance learning. Distance education. Extrapolation of trends and linear regression. Future studies.